Challenges Faced by Instructors in Implementing Non-Formal Islamic Religious Education Integrated with Religious Moderation in Suro Bali Village, Ujan Mas Sub-District, Kepahiang Regency - Sibuan Sibuan; Hendra Harmi; Sutarto Sutarto; Aida Rahmi Nasution (Yayasan Darusssalam Bengkulu, 2026)
This study investigates the challenges faced by non-formal Islamic education instructors in integrating religious moderation (moderasi beragama) values at the village level. Conducted in Suro Bali Village, Ujan Mas Sub-district, Kepahiang Regency — a unique community where Muslim and Hindu residents coexist harmoniously — this research employs a descriptive qualitative approach through observation, documentation, and in-depth interviews with 17 students and 3 instructors. The findings reveal that non-formal Islamic Education (PAI) in Suro Bali is implemented through a textual-contextual approach that connects Quranic teachings with local social realities. However, instructors face significant internal problems, including limited methodological competence in teaching moderation creatively, psychological burdens in maintaining narrative neutrality, and dual-role workloads as community figures. External challenges include a lack of contextual teaching modules relevant to the local multicultural setting, minimal digital infrastructure, and insufficient institutional support in the form of structured training for non-formal instructors. Despite these constraints, instructors independently improvise using local wisdom as instructional media, maintain personal dialogue with Hindu religious leaders, and develop digital literacy as a counter-narrative to intolerant content on social media. This study recommends structured capacity-building programs for non-formal Islamic education instructors in religiously diverse rural areas.